The Impact of IPPs in Developing Countries : Out of the Crisis and into the Future - Albouy, Yves (World Bank, Washington, DC, 2012)
Developing countries started opening their power sectors to independent power producers (IPPs) some ten years ago, and IPPs have now developed into a large market. This Note examines several contentious questions relating to the developing of this market: Has risk been transferred to the private sector, or have IPPs contributed to an increase in government liabilities? Have IPPs contributed an increase in foreign exchange exposure? Are pricing and investment decisions efficient? Have IPPs contributed to sector modernization? Answering these questions has become more pressing with the global financial crisis. The Note concludes that on the whole IPPs have had a positive development impact. But negative effects become significant when the IPP program quickly grows to a large size relative to the host grid capacity, as has happened in a few Asian countries.